2022
DOI: 10.1002/1873-3468.14411
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic modulation and analysis of islets of Langerhans in living zebrafish larvae

Abstract: Microscopic analysis of molecules and physiology in living cells and systems is a powerful tool in life sciences. While in vivo subcellular microscopic analysis of healthy and diseased human organs remains impossible, zebrafish larvae allow studying pathophysiology of many organs using in vivo microscopy. Here, we review the potential of the larval zebrafish pancreas in the context of islets of Langerhans and Type 1 diabetes. We highlight the match of zebrafish larvae with the expanding toolbox of fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…Many methods, including genetic mutation, chemical induction and dietary alteration, have been used for inducing metabolic disease models in zebrafish [ 24 , 25 ]. Recently, studies on pancreas development and modulation in zebrafish have been applied as a model for diabetes and indicate that this model is closely associated with diabetes [ 26 , 27 ]. In addition, it was confirmed that the studies using zebrafish are a good animal model for diabetes research from the efficacy of glimepiride, a common drug for the treatment of diabetes, and it is used as a positive control in previous studies [ 13 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many methods, including genetic mutation, chemical induction and dietary alteration, have been used for inducing metabolic disease models in zebrafish [ 24 , 25 ]. Recently, studies on pancreas development and modulation in zebrafish have been applied as a model for diabetes and indicate that this model is closely associated with diabetes [ 26 , 27 ]. In addition, it was confirmed that the studies using zebrafish are a good animal model for diabetes research from the efficacy of glimepiride, a common drug for the treatment of diabetes, and it is used as a positive control in previous studies [ 13 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The beauty of zebrafish larvae is the possibility of exploring the fundamentals of organ development and malfunction in vivo . This model system also allows easy genetic modifications ranging from transient knockdowns to transgenic models or the integration of genetically encoded fluorescent proteins in knock‐in models [1]. The review also illustrates two microscopic approaches, confocal microscopy, and light sheet imaging, useful to visualize the subcellular localization of specific fluorescent markers.…”
mentioning
confidence: 99%